2006
DOI: 10.1111/j.1600-9657.2006.00338.x
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of first‐aid measures of avulsion and replantation of teeth: an interview of 221 Kuwaiti schoolchildren

Abstract: The prognosis of replantation of an avulsed tooth is determined by which first-aid measures are taken during the first 15 min after avulsion. Knowledge of the correct first-aid measures is therefore crucial to successful replantation. The aims of this study were (i) to assess the present knowledge level of emergency measures for tooth avulsion in Kuwaiti schoolchildren, and (ii) to design and test an interview form with structured standardized questions. A total of 221 Kuwaiti schoolchildren (aged 7-15 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 23 publications
6
78
0
1
Order By: Relevance
“…For measures to be taken in cases of tooth extraction, 24% of the respondents said they did not know what to do to help the child and 70% said they would not replanted the tooth. In this study there was a low rate of dental replantation, as in other studies in the Table III (continued) literature [4,12]. Although 75% of teachers answer correctly that the avulsed tooth should be handled by the crown and 55% respond that would wash in running water abundantly, few would realize the dental reimplantation.…”
Section: Discussionsupporting
confidence: 45%
“…For measures to be taken in cases of tooth extraction, 24% of the respondents said they did not know what to do to help the child and 70% said they would not replanted the tooth. In this study there was a low rate of dental replantation, as in other studies in the Table III (continued) literature [4,12]. Although 75% of teachers answer correctly that the avulsed tooth should be handled by the crown and 55% respond that would wash in running water abundantly, few would realize the dental reimplantation.…”
Section: Discussionsupporting
confidence: 45%
“…Dry storage of the tooth will result in an irreversible injury to the periodontal membrane, with the result that the replanted tooth will be lost over time. Storage media like saline, milk, balanced salt solution with osmolality similar to the tissue fl uid do not destroy the periodontal ligament cells 31 . Majority (53.1%) didn't have any idea on medium required for storage/transportation of knocked out teeth similar to study done by Mohandas et al 21 whose fi nding was 58.3%.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study in Kuwait, it was shown that children have a low level of knowledge about avulsed teeth [31] . Although many of the children had received general first-aid information, dental injuries were not included [31] .…”
mentioning
confidence: 99%
“…Most studies on lay knowledge of tooth avulsion indicate that the level of knowledge is low [21][22][23][24][25][26][27][28][29][30][31] . In a recent study in Kuwait, it was shown that children have a low level of knowledge about avulsed teeth [31] . Although many of the children had received general first-aid information, dental injuries were not included [31] .…”
mentioning
confidence: 99%